Новые виды четырехногих клещей (Acari, Eriophyoidea) с амброзии, земляничного дерева и папоротника - Лившиц, И.З.; Митрофанов, В.И.; Шаронов, А.А. (Вестник зоологии, 1983)
Four Ambrosia, Arbutus and Pleridium dwelling fetrapod mite species from Crimea and Caucasus are described as new. Aceria izhevskii sp. n.— similar to A. boissieri (Roiv.), differs by the presence of six cheloidal pairs and widely rounded dorsal shield anterior margin. Artacris fusiformis sp. n.— similar to American A. anfonimus (K) and European A. macrorhynchus (Nal), differs by the presence of five chetoidal pairs, dorsal shield ‘ornamentation and granulated lateral fields of the prodorsum and sterniocoxal area. Abacarus andrachni sp. n.— similar to A. histrix (Nal), differs by wider smooth dorsal shield and genital valva, lower number of empodial chaetoids and heterosegmented body. Eriophyes parapteridis sp. n.— similar to E. helicantix (K.), differs by orientation and shorter dimensions of dorsal and genital chaetae.